Analytical Method Development: A Review - Bandawane, Akash; Saudagar, Ravindranath (Journal of Drug Delivery and Therapeutics, 2019)
The oldest form of medicine known to mankind is herbal medicine. Today, it is the most widely practiced form of medicine in the world. Using medicinal plants for treatment is considered very safe as there is no or minimal side effects. Most of the plant materials collected from the rain forests and other places are currently used for conducting extensive research for their potential medicinal value. In Ayush systems of medicine about 8,000 herbal drugs have been codified 2. One of them is Coriandrum sativum Linn. belongs to the family Apiaceae and commonly known as kishneez khushk in Unani medicine.3It possesses multiple pharmacological activities which are revealed previously, such as anxiolytic, antidepressant, sedative-hypnotic, neuroprotective, antibacterial, antifungal, anthelmintic, insecticidal, antioxidant, cardiovascular, analgesic, anticonvulsant, memory enhancing, antidiabetic, anticancer, gastrointestinal, deodorizing, dermatological, hypolipidemic, anti-inflammatory, diuretic, reproductive, hepatoprotective, antimutagenic, detoxification etc4,14. The current review gives an overview of the pharmacological effects and chemical constituents of Coriandrum sativum. Keywords: Coraindrum sativum Linn. herbal medicine, pharmacological activities.